Discreteness of subgroups of SL(2,C) containing elliptic elements - Tukia, Pekka; Wang, Xiantao (MATHEMATICA SCANDINAVICA, 2002)
The following result is the main result of the paper. Let GSL(2,C) be non-elementary. If G contains an elliptic element of order at least 3, then G is discrete if and only if each non-elementary subgroup generated by two elliptic elements of G is discrete.